Studi Penggunaan Alat Pengolahan Lahan Pada Budidaya Padi Sawah di Kecamatan Gambut Kabupaten Banjar - Hafizh, Muhammad; Suparto, Hairu; Sofyan, Antar (Universitas Lambung Mangkurat, 2025)
Gambut district is one of the largest producers of local rice in Banjar Regency. The potential of rice fields in Gambut district covers an area of 7,000 hectares. Rice fields in Gambut districts are included in overflow type C and D land with a direct source of irrigation from rainwater or called rainwater. The majority of farming communities in peat sub-districts plant local varieties of rice with a planting period of one planting a year. Farmers in peat sub-districts cultivate rice paddies from land preparation to harvest for approximately ten months. Land preparation is the first step that needs to be done in the rice cultivation stage. Land preparation is carried out using tools and techniques that are in accordance with the characteristics and conditions of the rice field that will be used for rice cultivation. The use of the right land cultivation tools and techniques can facilitate the process of rice cultivation carried out by farmers. This study uses direct observation methods in rice fields and interviews with local rice farmers in two villages, namely Malintang and Tambak Sirang Laut, Gambut District, Banjar Regency. The results of the research are in the form of interviews and field documentation presented in the form of descriptive tabulation. The results of the study showed that farmers in Malintang and Tambak Sirang Laut Villages, Gambut District, each farmer used different land tillage techniques, the results of the study also showed that the harvest from farmers who cultivated the land using traditional techniques and tools was more than the maximum tillage technique using hand tractors. The application of paraquat herbicide in land cultivation also affects soil fertility so that it has an impact on the results that will be harvested later.